Government Policy in Tackling Unemployment - Sihombing, Andy Tonggo Michael; Sitorus, Rolib (PT FORMOSA CENDEKIA GLOBAL, 2024)
Unemployment is one of the serious and complex economic problems, which affects the welfare of individuals and the social stability of a country. To overcome this challenge, governments often implement various policies aimed at reducing unemployment rates. These policies can be divided into three main categories: macroeconomic policies, labor market policies, and training and education policies. Based on these things, this paper is conducted to determine the impacts arising from the effects of unemployment, and to determine government policies in overcoming unemployment. This paper is carried out by collecting materials using library research methods and tracing various sources of literature on policies taken by the government. While the results obtained in this paper are the impacts arising from the effects of unemployment on individuals, namely financial difficulties, stress and mental health problems, decreased self-confidence and decreased skills; on society, namely increased inequality, decreased quality of life; on the economy, namely decreased consumption, decreased tax revenues, increased social and health costs, and government policies in overcoming unemployment in various fields including fiscal and monetary policies, increasing foreign investment, investment promotion, trade and industrial policies, developing SMEs, developing the tourism sector and indigenous Indonesian culture, providing guarantees for workers whose employment is terminated (PHK), employment policies.